O neoliberalismo na educação pública alagoana durante o governo Teotonio Vilela (2007 a 2015) - Lira, Jailton de Souza (2016)
This thesis analyzes the consequences of the neoliberal management of government Teotonio Vilela (2007-2011; 2011-2015) for the state public education in Alagoas in the context of political, economic and social situation resulting from the capitalist system reshaping process in the midst of their crisis structural started in the last decades. In Alagoas public education, specifically investigates the consequences of neoliberalism in the quality of teaching, the management model and implemented financing, training and development of professionals in education, and reflect on the actual working conditions of these professionals. So this thesis focuses mainly on the assessment of one of the main Brazilian public policy. It is a qualitative research and methodologically uses the contributions of historical and dialectical materialism. The discussion on the consequences of the implementation of neoliberalism in education in Alagoas articulates the broader debate of political and economic reformulations observed in Brazil from the strengthening of neoliberal ideals over the years 1990 and 2000, which was evidenced both character neoliberal of Vilela Filho management as the damage to the quality of state public education